Ultraviolet radiation in the Arctic - The impact of potential ozone depletions and cloud effects - Tsay, Si-Chee; Stamnes, Knut (1992)
The combined effects of ozone depletions/redistributions and particulate clouds on atmospheric cheating/photolysis rates and UV radiation reaching the biosphere are investigated by means of an atmospheric radiation model. Consideration is given to four types of particulate clouds prevalent in the summertime Arctic: stratospheric aerosols, tropospheric aerosols (Arctic haze), cirrus clouds, and stratus clouds. The effects of ozone depletion and vertical redistributions of ozone are also examined. Stratus clouds are found to provide significant protection from UV radiation exposure, but while stratospheric aerosols imply increased UVB exposure, Arctic haze results in a decrease. A redistribution of ozone from the stratosphere to the troposphere tends to decrease UV exposure, but for low solar elevations an increase may occur. A 20-percent ozone depletion leads to about 0.4 K/d cooling in the lower stratosphere, while redistribution of ozone from the stratosphere to the troposphere implies a warming of about 0.015 K/d in the upper troposphere.